2000
DOI: 10.1002/(sici)1097-0134(20000201)38:2<189::aid-prot7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of a peptide model of a region important for the folding of ?-lactalbumin provides evidence for the formation of nonnative structure in the denatured state

Abstract: Elucidating the properties of the denatured state of proteins under conditions relevant for their folding is a key factor in understanding the folding process. We show that a peptide corresponding to residues 111-120 of human alpha-lactalbumin has a pronounced propensity to adopt nonnative structure in aqueous solution. Two-dimensional NMR provides evidence for a structured, nonnative conformation in fast exchange with a random coil ensemble. A total of 78 Rotating Frame Overhauser Effects (ROEs) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Consistently, there is a local minimum fragment 48-105 with a score of 2.94 in the complete list of 20 local minima of the fragment map (not shown). Fifth, the 111-120 peptide populates a nonnative structured conformation, in rapid exchange with a random coil state in aqueous solution (26). This further supports fragment 106-123 (with a score of Ϫ9.10 as compared with the score of fragment 3-38, Ϫ0.53) as being stabilized in its native conformation by associating with fragment 3-38.…”
Section: Resultsmentioning
confidence: 93%
“…Consistently, there is a local minimum fragment 48-105 with a score of 2.94 in the complete list of 20 local minima of the fragment map (not shown). Fifth, the 111-120 peptide populates a nonnative structured conformation, in rapid exchange with a random coil state in aqueous solution (26). This further supports fragment 106-123 (with a score of Ϫ9.10 as compared with the score of fragment 3-38, Ϫ0.53) as being stabilized in its native conformation by associating with fragment 3-38.…”
Section: Resultsmentioning
confidence: 93%
“…36 -38 Peptides encompassing residues 101-111 and 101-120 of the a-LA sequence do show some degree of helicity in aqueous solution but the latter appears to be largely non-native in character. 39,40 A peptide consisting of residues 1 -38 and 95 -120 cross-linked by the C28 -C111 disulfide bond, however, shows not only significant helical structure but also characteristics of a molten globule including the enhancement of ANS fluorescence. 41 Deletion of residues 95 -100 has little effect on the structure in this peptide, indicating that the C-helix is not important for the stability of its molten globule structure.…”
Section: Discussionmentioning
confidence: 99%
“…We have used a protein dissection approach to examine the role‐specific regions of the protein chain play in stabilizing structure within the α‐domain of human α‐lactalbumin 11–14. The α‐domain contains 4 α‐helices denoted A through D as well as a 3 10 helix.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest that 1 H NMR studies of two peptides consisting of residues 101–111 and 111–120 of αLA have shown that these fragments have significant propensity to form remarkably well‐defined, locally stabilized, non‐native structure. The structure is localized within residues 101–105 and residues 115–12011, 14, 15 and is stabilized by non‐native clusters of hydrophobic residues. Most of the contacts between the C‐terminal portion of the protein and the B‐helix are formed by residues contained within these two clusters.…”
Section: Introductionmentioning
confidence: 99%